Psychological barriers in intercultural communication (Pedagogy of Higher and Secondary Education, 2014)
Dyrda I. A. Psychological barriers in intercultural communication. The essence of psychological barriers is explored in the paper; views of native and foreign scientists on current problem are analysed; the meaning of notions «dialogue of cultures», «communication» and «intercultural communication» is exposed in the paper.
Keywords: dialogue of cultures; cultural differences; communication; intercultural communication; tolerance; ethnocentrism; stereotypes